ALRChap11 - Chapter 11: Nonlinear Regression Example 1: Y=1...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Chapter 11: Nonlinear Regression Example 1 : Y= θ 1 + θ 2 (1- (1/exp( θ 3 x))) + e Example 2 : Y= β 0 + β 1 βψ s (x, λ ) In general, Y=m(x, θ ) + e Where m is a known function (kernel mean function) n RSS( θ )= Σ (y i -m(x i , θ )) 2 i=1 One term Taylor expansion: m( θ ,x i ) m( θ * , x i ) + u i ( θ * )c (θ - θ * ) Thus, n RSS( θ ) Σ [(y i -m( θ * ,x i )- u i ( θ * ))c ( θ - θ * )] 2 i=1 n = Σ [(ê * - u i ( θ * ) )c ( θ - θ * )] 2 i=1
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 12/12/2010 for the course STAT 425 taught by Professor Ma,p during the Fall '08 term at University of Illinois, Urbana Champaign.

Ask a homework question - tutors are online